Screening of Foeniculum Vulgare L, Coriandrum Sativum L, Pegnum Harmala L. and Achilleae Millefolium L Collected from Balochistan Against Fungi Causing Onychomycosis - Nida Jamshaid, Shahida Liaqat, Noureen Khan, Syma Arshad, Mehreen Saba, Bibi Sadia, Zeeshan Khan, Shagufta Rasool, Ameena Bibi, Aroosa Habib, Wajia Noor (Pakistan Journal of Medical & Health Sciences, 2022)
Onychomycosis is referred to as fungal nail infection or toe nail infection generally caused by Trichophyton, Candida albicans , Microsporum and Aspergillus species. The Aim of the study was to investigate antifungal potential of four medicinal flora of Balochistan namely, Foeniculum vulgare L. , Coriandrum sativum L. , Pegnum harmala L. and Achilleae milefolium L. against causative fungal strain of nail infection. Different fractions were prepared using different solvents such as hexane, chloroform and ethyl acetate and antifungal activity was determined through agar well diffusion method against fungal strain candida albicans. For the qualitative determination of phytochemical composition different tests were carried out including tests for alkaloids, terpenoids , carbohydrates, glycosides, proteins, steroids, saponins, phenols and tannins. The highest inhibition zone were observed in aqueous 80% crude methanolic extracts of Foeniculum vulgare L. i.e 26 mm and Coriandrum sativum L. 30mm respectively. Aqeous layer of the crude extract of both plants showed potent activity that were 24 mm and 25mm for Foeniculum L. vulgare and Coriandrum sativum L.. the ethylacetet fractions showed inhibition zone 19mm and 18mm in Foeniculum vulgare L. and Coriandrum sativum L. Chloroform and hexane fractions showed least activity against fungi causing onychomycosis. An Antifungal activity highest inhibition zones were observed in aqueous 80% crude methanolic extracts of Pegnum harmala L. i.e 39 mm and Achilleae millefolium 34 mm respectively. Aqeous layer of the crude extract of both plants showed potent activity that were 32 mm for Pegnum harmala L. and 25mm for Achilleae millefolium L. The choloroform fractions showed inhibition zone 19mm in Pegnum harmala L. while 16mm in Achilleae millefolium L. Hexane and ethyl acetate fractions of Pegnum harmala L. and Achilleae millefolium L. showed least activity against fungi causing onychomycosis.